2009
DOI: 10.1002/tl.346
|View full text |Cite
|
Sign up to set email alerts
|

Preparing STEM doctoral students for future faculty careers

Abstract: This chapter describes programs created to improve the preparation of future STEM faculty for their roles as educators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 5 publications
1
72
0
Order By: Relevance
“…Many studies in the last decade have explored professional development approaches that may support the preparation of engineering doctoral students for academic careers or other careers that include teaching (e.g., Austin and colleagues 1,7 ). These studies highlight key factors that may affect a program's impact on a graduate student's overall experience within the program and after.…”
Section: Experiences Of Engineering Graduate Students In Academic Carmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies in the last decade have explored professional development approaches that may support the preparation of engineering doctoral students for academic careers or other careers that include teaching (e.g., Austin and colleagues 1,7 ). These studies highlight key factors that may affect a program's impact on a graduate student's overall experience within the program and after.…”
Section: Experiences Of Engineering Graduate Students In Academic Carmentioning
confidence: 99%
“…These studies highlight key factors that may affect a program's impact on a graduate student's overall experience within the program and after. The use of learning communities 1,7,13 and opportunities to network with faculty members 3 , for example, have been shown to support students' development as educators and their overall preparation for academic careers. In addition, research has identified areas for improvement in these programs, including a need for increased mentoring 6,14 , more explicit feedback 1 , and additional autonomy in the classroom 13,15 .…”
Section: Experiences Of Engineering Graduate Students In Academic Carmentioning
confidence: 99%
See 3 more Smart Citations